LANGUAGE AND GENDER: HOW LANGUAGE SHAPES GENDER ROLES - Sabina Raimberdiyeva Elyor qizi; Mavlyuda Komiljonova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The relationship between language and gender is examined in this thesis, which looks at how linguistic practices support, maintain, and challenge gender roles in society. Using theories from discourse analysis, gender studies, and sociolinguistics, the study investigates how language affects how people perceive femininity, masculinity, and other gender identities. The study illuminates how gendered language may both reflect and reinforce social norms while also offering a forum for questioning them by examining actual instances from everyday discourse, media portrayals, and institutional language. The thesis contends that language actively shapes the construction and maintenance of gender roles rather than only reflecting preexisting gender systems. By indicating that linguistic practices are important in the negotiation and reinforcement of gender identities in modern society, this research advances our knowledge of the dynamic relationship between language and gender.